Prevalence of dizziness in the population of Minas Gerais, Brazil, and its association with demographic and socioeconomic characteristics and health status - Martins,Tiago Ferreira (2017)
Abstract Introduction The state of Minas Gerais, Brazil has no data on the prevalence of dizziness in the population and this information can be fundamental as the basis of public health policies, promotion, prevention and rehabilitation campaigns. Objective Investigate the prevalence of the symptom of dizziness in the population of Minas Gerais according to Sample Survey of Households, as well as describe the profile of interviewed individuals and the association between dizziness and socioeconomic, demographic features and health status. Methods This was a cross-sectional observational study that analyzed individuals with dizziness symptom reported in the previous month. The data entered in the Sample Survey of Households of 2011 were analyzed. An independent statistical association was determined between the selected variables and dizziness through multivariate analysis. Results Dizziness was the third major complaint among individuals who mentioned any health problems in the previous month, with an estimated population of 209,025 individuals and reported by 6.7% of symptomatic ones, with higher prevalence values only reported for the symptoms of fever and headache. Among individuals who reported dizziness, 94% were adults or elderly (p ≤ 0.001) and 63% were females (p = 0.003). A statistically significant association (p < 0.001) was observed between the response variable and the variables: self-perceived health, hypertension, heart disease, diabetes, depression, seeking or requiring medical or health care in the previous month and private health care plan or insurance. Among individuals with dizziness, 84.2% sought or required medical or health care and 80.1% did not have a private health plan or insurance in the assessed period. Conclusion The dizziness symptom was highly prevalent in the population of Minas Gerais during the assessed month of the investigation. Dizziness was prevalent in adults and the elderly and showed a statistical association with socioeconomic and demographic characteristics, as well as the assessed health status.